PENGARUH STRATEGI PEMECAHAN MASALAH UNTUK MENINGKATKAN KETERAMPILAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL DI SMA - Istiqomah, Fahimatul; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe study examines the effect of problem solving strategy to improve the student?s skill of solving the problem on momentum and impulse. The method of this research is pre-experimental design (one group pretest-posttest design) with 30 students of X MIPA 3 grade at SMAN 2 Pontianak for participant which has taken by purposive sampling technique. The 4 problems on essay test used in this research. Based of the results, problem solving skills of the student is 21.33% on low category and 69% on high category respectively on pretest and posttest. It improved on medium category with N-gain score 0.607. Wilcoxon test showed significant difference of problem solving skills after momentum and impulse learning with problem solving strategy. The effectivity of this strategy in improving problem solving skills is 6,12 (high level). The results of this study are expected to be an alternative in an effort to improve the physics? problem solving skills of the student using problem solving strategy. Keywords:  problem solving strategy, physics? problem solving skill, momentum and impulse